2021
DOI: 10.3390/app11083420
|View full text |Cite
|
Sign up to set email alerts
|

Structural Health Monitoring of Walking Dragline Excavator Using Acoustic Emission

Abstract: The article is devoted to the organization of the structural health monitoring of a walking dragline excavator using the acoustic emission (AE) method. Since the dragline excavator under study is a large and noisy industrial facility, preliminary prospecting researches were carried out to conduct effective control by the AE method, including the study of AE sources, AE waveguide, and noise parameters analysis. In addition, AE filtering methods were improved. It is shown that application of the developed filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In [25], it was shown that the distribution of AE signal amplitudes corresponds to the Weibull law W(λ,k). The parameters of scale λ and shape k are random values corresponding to the normal distribution law for each of the inspected materials.…”
Section: Ae Source Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In [25], it was shown that the distribution of AE signal amplitudes corresponds to the Weibull law W(λ,k). The parameters of scale λ and shape k are random values corresponding to the normal distribution law for each of the inspected materials.…”
Section: Ae Source Modelingmentioning
confidence: 99%
“…Considering the results of the preliminary study, a hierarchical two-level algorithm is proposed for modeling the AE source (Figure 4), in which the distribution parameters for λ, k and D a are estimated first, and then the parameters of the AE source are determined, characterizing its emissivity and amplitude values of radiated AE signals. In [25], it was shown that the distribution of AE signal amplitudes corresponds to the Weibull law W(λ,k). The parameters of scale λ and shape k are random values corresponding to the normal distribution law for each of the inspected materials.…”
Section: Ae Source Modelingmentioning
confidence: 99%